Genome-wide association studies of doubled haploid exotic introgression lines for root system architecture traits in maize (Zea mays L.). (March 2018) - Sanchez, Darlene L.; Liu, Sisi; Ibrahim, Rania; Blanco, Michael; Lübberstedt, Thomas
Highlights: Considerable variation was observed for seedling root traits among exotic by elite-derived doubled haploid lines. Significant trait associations involving the SNP S5_152926936 in Chromosome 5 were detected in three GWAS models. Some SNPs were in linkage disequilibrium with known QTL for root development on Chromosomes 1, 2, 5, and 7. Various SNPs on Chromosomes 2, 7, and 8 may be associated with root development in maize, based on in silico data. Abstract: Root system architecture (RSA) is becoming recognized as important for water and nutrient acquisition in plants. This study focuses on finding single nucleotide polymorphisms (SNPs) associated with seedling RSA traits from 300 doubled haploid (DH) lines derived from crosses between Germplasm Enhancement of Maize (GEM) accessions and inbred lines PHB47 and PHZ51. These DH lines were genotyped using 62, 077 SNP markers, while root and shoot phenotype data were collected from 14-day old seedlings. Genome-wide association studies (GWAS) were conducted using three models to offset false positives/negatives. Multiple SNPs associated with seedling root traits were detected, some of which were within or linked to gene models that showed expression in seedling roots. Significant trait associations involving the SNP S5_152926936 on Chromosome 5 were detected in all three models, particularly the trait network area. The SNP is within the gene model GRMZM2G021110, which is expressed in roots at seedling stage. SNPs that were significantly associated with seedling root traits, and closely linked to gene models that encode proteins associated with root development were also detected. This study shows that the GEM-DH panel may be a source of allelic diversity for genes controlling seedling root development.